Magnetic Resonance Imaging and Flexible Hysterofiberscopic Findings of a Uterine Adenofibroma: Case Report and Literature Review - Hideki Watanabe; Naoya Harada; Ichiro Nobuhara; Noriko Haruta; Yumi Higashiura; Shioka Watanabe (Case Reports in Obstetrics and Gynecology)
To our knowledge, highly detailed findings of flexible hysterofiberscopy in patients with adenofibroma have not been described. A 75-year-old nulliparous asymptomatic woman presented with a uterine polyp, which exhibited punctate heterogeneous hyperintensity or islands of isointense-to-hypointense signals on T2-weighted magnetic resonance imaging (MRI), hypointense signals on T1-weighted images (T1WI), and a little enhancement on contrast-enhanced T1WI. Flexible hysterofiberscopy revealed a red-pink polyp with a white-yellow, cobblestone-like surface easily deformed by perfusion fluid. The tumor was diagnosed histologically as an adenofibroma. Total abdominal hysterectomy and bilateral salpingo-oophorectomy were performed. The tumor in the uterus was necrotic macroscopically and histologically, and a residual adenofibroma could not be confirmed. At present, two years after surgery, the patient remains healthy. MRI and hysterofiberscopy can reveal the histological features of uterine adenofibromas and be useful for their diagnosis.